Love in the Time of COVID: Perceived Partner Responsiveness Buffers People From Lower Relationship Quality Associated With COVID-Related Stressors. Issue 3 (April 2023) - Balzarini, Rhonda N.; Muise, Amy; Zoppolat, Giulia; Di Bartolomeo, Alyssa; Rodrigues, David L.; Alonso-Ferres, María; Urganci, Betul; Debrot, Anik; Bock Pichayayothin, Nipat; Dharma, Christoffer; Chi, Peilian; Karremans, Johan C.; et al.
External stressors can erode relationship quality, though little is known about what can mitigate these effects. We examined whether COVID-related stressors were associated with lower relationship quality, and whether perceived partner responsiveness —the extent to which people believe their partner understands, validates, and cares for them—buffers these effects. When people in relationships reported more COVID-related stressors they reported poorer relationship quality at the onset of the pandemic ( N = 3, 593 from 57 countries) and over the subsequent 3 months ( N = 1, 125). At the onset of the pandemic, most associations were buffered by perceived partner responsiveness, such that people who perceived their partners to be low in responsiveness reported poorer relationship quality when they experienced COVID-related stressors, but these associations were reduced among people who perceived their partners to be highly responsive. In some cases, these associations were buffered over the ensuing weeks of the pandemic.